Field measurement and analysis of ship generated waves in Hooghly river, India. (November 2022) - Chakraborty, Mainak; Sriram, V.; Murali, K.
Abstract: Vessel movements in restricted waterways disturb the natural flow field and generate waves that create complex hydrodynamics. It is difficult to understand the general characteristics of ship-generated waves in restricted channels due to non-linearity and local bathymetry. A field study on the Hooghly river was conducted to assess and analyse the ship-generated primary and secondary waves. This paper investigated the wake signal from the field survey employing time-frequency analysis (short-term Fourier transform). The spectrogram study identified the primary and secondary waves from the wake signal. In comparison with the linear dispersion curve, the time-frequency study helps identify the divergent and transverse waves from the wave signal. The spectrogram study helps understand the influence of non-linearity from ship waves with increasing velocity. The energy content on the different components of the ship waves revealed the erosive potential of the waves. The measured primary and secondary waves were compared with the existing empirical relations, but satisfactory results were not obtained. Hence, a new empirical relationship between the primary and secondary waves has been obtained based on understanding the physical processes from the analysis of field data. Highlights: The paper studies the ship-generated hydrodynamics by means of field measurements. The dispersion curve helps to understand the non-linearity of ship-wave components. A new empirical relationship for primary and secondary waves has been presented. Parametric study of the ship waves with critical parameters are explored.